Mechanical circulatory support in patients in cardiogenenic shock - Tanskyi, V. H. (Modern medical technology, 2025)
Cardiogenic shock in acute myocardial infarction is a life-threatening syndrome characterized by systemic hypoperfusion that can rapidly progress to multiple organ failure and death. There are various mechanical circulatory support devices and configurations available to support patients, each with unique pathophysiological characteristics. The aim. To investigate the effectiveness and causes of adverse outcomes of extracorporeal membrane oxygenation in the treatment of patients with cardiogenic shock. Materials and methods. Between January 2024 and December 2024, 11 patients underwent venous-arterial extracorporeal membrane oxygenation in the state of cardiogenic shock at the Kovel-ECMO hospital district. Results The survival rate was 72.0 % (8 patients). The successful cannulation rate was 100 %. The median cannulation time was 15 minutes. The median time before extracorporeal membrane oxygenation was 54 minutes. The median age was 50 years, and 100 % were male. Conclusions. When using temporary mechanical circulatory support in patients with cardiogenic shock, a positive result was obtained in 72.0 % of patients.